2013
DOI: 10.1177/1756283x13491798
|View full text |Cite
|
Sign up to set email alerts
|

A 9-year evaluation of temporal trends in alosetron postmarketing safety under the risk management program

Abstract: Over the 9-year RMP period, incidence rates of IC and CoC remain rare. Substantial reductions over time were observed in the incidence of CoC and in symptoms suggestive of IC or CoC, while IC incidence has been stable at approximately 1.0 case/1000 patient-years. Decreases in AEs and serious outcomes associated with IC and CoC since the reintroduction of alosetron are likely attributable to the RMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…adequate relief), specific symptoms 2, 3 , quality of life, and reversing the restriction of daily activities 8 . However, these were either withdrawn from the market (alosetron) or never marketed (cilansetron) due to concerns of complications of severe constipation and reports of ischemic colitis (0.6 and 1.1 per 1000 patient-years respectively); these rates of complications were confirmed in the analysis of data in the risk management program 9 . However, the pathobiological mechanisms of the ischemic colitis are unclear 10, 11 , and it is still not completely resolved whether the risk is entirely due to the medication or related to IBS per se (independent of serotonergic therapies), since several population-based studies demonstrated that a diagnosis of IBS increases the risk of developing ischemic colitis 2- to 4-fold (reviewed in 12 ).…”
mentioning
confidence: 98%
“…adequate relief), specific symptoms 2, 3 , quality of life, and reversing the restriction of daily activities 8 . However, these were either withdrawn from the market (alosetron) or never marketed (cilansetron) due to concerns of complications of severe constipation and reports of ischemic colitis (0.6 and 1.1 per 1000 patient-years respectively); these rates of complications were confirmed in the analysis of data in the risk management program 9 . However, the pathobiological mechanisms of the ischemic colitis are unclear 10, 11 , and it is still not completely resolved whether the risk is entirely due to the medication or related to IBS per se (independent of serotonergic therapies), since several population-based studies demonstrated that a diagnosis of IBS increases the risk of developing ischemic colitis 2- to 4-fold (reviewed in 12 ).…”
mentioning
confidence: 98%
“…Because of the risk of severe constipation and ischemic colitis in some patients, prescribing of alosetron is limited to healthcare providers enrolled in a special prescribing program, and patients must sign an acknowledgment form before initiating treatment [Prometheus Laboratories, Inc., 2014;Chang et al 2010;Schiller and Johnson, 2008]. Analysis of postmarketing data acquired after implementation of the risk management program demonstrated that the incidence of ischemic colitis and constipation remained rare and decreased between 2002 and 2011 [Tong et al 2013]. Another 5-HT 3 receptor antagonist, ondansetron, has also been shown to improve symptoms in patients with IBS-D.…”
Section: Management Of Ibs: Established Approachesmentioning
confidence: 99%
“…Overall use of the drug fell substantially, as did reports of intestinal complications. 37 As of mid-2014 there were eighty-one REMS in effect, thirty-nine of which included elements to ensure safe use. About half of these thirty-nine were for specialty drugs.…”
Section: Limiting Overusementioning
confidence: 99%